Analysis of AI Technology Utilization in Islamic Education: Analisis Pemanfaatan Teknologi AI dalam Pendidikan Islam - Resky, Muhammad; Suharyat, Yayat (Procedia of Social Sciences and Humanities, 2024)
The advancement towards Society 5.0 and the rapid development of technologies, exemplified by generative AI systems like ChatGPT, highlight significant changes in various domains, including education. This evolution in artificial intelligence (AI) presents both opportunities and challenges, particularly in the realm of Islamic education.ChatGPT, developed by OpenAI, represents a sophisticated AI tool capable of generating human-like text through advanced algorithms and natural language processing. While its ability to provide quick and accurate information has revolutionized many fields, its impact on Islamic education necessitates careful consideration, given the traditional reliance on qath'i (definitive) sources for religious knowledge.Despite the extensive capabilities of AI tools like ChatGPT, there is limited empirical research on their application and implications within Islamic educational contexts, particularly concerning the adherence to traditional scholarly methods and the preservation of sanad (chain of transmission) in Islamic knowledge.This study aims to explore the integration of ChatGPT in Islamic education, focusing on its potential benefits and limitations. It evaluates how AI tools can be effectively utilized while maintaining the integrity of Islamic educational principles and ethical standards.